2002
DOI: 10.1074/jbc.m203380200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 Is a Ligand-independent Co-repressor for Thyroid Hormone Receptors

Abstract: Thyroid hormone receptors (TRs) are critical regulators of growth, differentiation, and homeostasis. TRs function by regulating the expression of thyroid hormone (T3) target genes in both ligand-dependent and -independent pathways. Distinct classes of co-regulatory proteins modulate these two pathways. We show here a novel role of cyclin D1 as a T3-independent corepressor for TRs. Cyclin D1 interacted with TR in vitro and in cells in a ligand-independent manner. Cyclin D1 acted to repress both the silencing ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 36 publications
2
60
1
1
Order By: Relevance
“…In addition, recent evidence suggests that cyclin D1 antagonizes the activity of the transcription factor, C/EBPb, in a cell cycle-independent fashion to contribute to the oncogenesis observed in overexpressing mammary carcinoma cells (Lamb et al, 2003). In contrast to its action in driving mammary oncogenesis and function as an ERa coactivator, cyclin D1 also acts as a potent corepressor of TRb1, PPARg, and AR (Lin et al, 2002;.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, recent evidence suggests that cyclin D1 antagonizes the activity of the transcription factor, C/EBPb, in a cell cycle-independent fashion to contribute to the oncogenesis observed in overexpressing mammary carcinoma cells (Lamb et al, 2003). In contrast to its action in driving mammary oncogenesis and function as an ERa coactivator, cyclin D1 also acts as a potent corepressor of TRb1, PPARg, and AR (Lin et al, 2002;.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it was demonstrated that cyclin D1 can bind to HDAC3 and recruit this repressor molecule to the TRb1 complex (Lin et al, 2002). Given our observation that the repressor domain is sufficient for corepressor activity, we hypothesized that HDAC3 may bind to this region of cyclin D1.…”
Section: Cyclin D1 Repressor Domain Is Sufficient For Ar Binding and mentioning
confidence: 99%
See 1 more Smart Citation
“…In specific cell types, cyclin D1 is found in association with the estrogen receptor a, thyroid hormone receptor, peroxisome proliferatoractivated receptor-g and the androgen receptor (AR) (Neuman et al, 1997;Zwijsen et al, 1998;Knudsen et al, 1999;Reutens et al, 2001;Lin et al, 2002;Petre et al, 2002;Petre-Draviam et al, 2003;Wang et al, 2003;Burd et al, 2005). With estrogen receptor, cyclin D1 can potentiate receptor activity independently of ligand and CDK4-kinase activity (Neuman et al, 1997), through formation of a ternary complex with estrogen receptor a and P/CAF, thereby altering chromatin structure to facilitate gene transcription (McMahon et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms are attributed to a discrete repressor domain, which binds to the AR N-terminus and prevents ligand-dependent conformational changes in AR . Additionally, this motif can recruit histone deacetylase 3 (HDAC3), and the AR-repressor function of cyclin D1 is dependent on HDAC function (Lin et al, 2002;Petre et al, 2002;Petre-Draviam et al, 2005). Concordantly, the repressor domain of cyclin D1 is also required for cyclin D1-mediated suppression of peroxisome proliferator-activated receptor-g activity (Fu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%